DYNAMICS OF CLINICAL INDICATORS OF POST-EXTRACTION WOUND HEALING UNDER THE CONDITIONS OF LOCAL USE OF CRYOPRESERVED PLACENTA - V.V. Khattou; K.P. Lokes; V.M. Havryliev; P.I. Yatsenko; I.V. Boyko; A.V. Tsybulniak; D.S. Avetikov (Український стоматологічний альманах, 2025)
After tooth extraction, the alveolar bone undergoes a remodeling process, which leads to a loss of bone quantity and a change in its quality. These processes lead to alveolar bone atrophy. To minimize bone tissue atrophy and reduce the likelihood of post-extraction complications, especially inflammatory ones, various means are used, such as PRP therapy, PRF, bone substitutes, etc. Also promising is the use of cryopreserved placenta, which has anti-inflammatory, antiangiogenic, antifibrotic and antimicrobial properties, and also enhances epithelialization.